Optimized TiO2 nanocrystallites aggregates for enhanced efficiency in dye solar cells - Zaine, S.N.A. (Trans Tech Publications Ltd, 2014)
TiO2 aggregates-based dye solar cells (DSCs) have gained an increasing attention due to their enhanced harvesting of light radiance. The capability of this photoelectrode material is attributed to the submicron spherical aggregates that introduce light scattering effect which can generate more electrons whilst high internal surface area for dye chemisorption is provided by nanocrystallites which made up the aggregates. Here, TiO2 aggregates (0.45-0.20 μm) composing of nanocrystallites (10-28 nm) with desired physicochemical properties for enhanced overall light conversion efficiency of DSC were synthesized by varying the water content in the hydrolysis of titanium alkoxide in ethanol and calcination temperature. TiO2 aggregates obtained were characterized using FESEM, XRD and UV-Vis spectroscopy. The assembled DSCs were then evaluated using solar simulator under AM 1.5 (100 mW/cm2) simulated sunlight. With higher water content in the hydrolysis process, the aggregates reduce in size and lose their spherical shapes resulting in lower absorption intensity indicating the occurrence of low light scattering in the TiO2 film. Nanocrystallites were found to have an increasing size of 12 nm to 28 nm with increasing calcination temperature of 400°C to 700°C. Sample of aggregates calcined at 450°C recorded the highest efficiency (~4). Highest conversion efficiency was observed for DSC that used welldefined spherical TiO2 aggregates composing of nanocrystallites which were synthesized at optimum synthesis parameter which is by using ethanol with low water content (0.9 vol) followed by calcination at 450°C. Thus, optimized TiO2 nanocrystallites which form spherical aggregate is critical in order to improve light harvesting efficiency of DSCs. © (2014) Trans Tech Publications, Switzerland.